1993
DOI: 10.1111/j.1432-1033.1993.tb18211.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural study of a cell‐wall mannan of Saccharomyces kluyveri IFO 1685 strain

Abstract: Acetolysis of the cell-wall mannan of Saccharomyces kluyveri under mild conditions, gave fragments with 1-6 mannose residues. The structures of mannopentaose and mannohexaose were determined to be Manal+3Manal-+2Manal+2Man 1 6 Manal and Manfil+2Manal+3Mannl+2Manal+2Man, FManal respectively, by two-dimensional homonuclear Hartmann-Hahn spectroscopy and a sequential NMR assignment method that combines 'H-I3C correlated spectroscopy, relayed coherence transfer spectroscopy, 'H-detected heteronuclear multiple-bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
43
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 44 publications
3
43
0
Order By: Relevance
“…Therefore, we can also assign through the H-1-H-2-correlated cross-peak C2 and the NOE cross-peak C2Ј between the H-2 of Man-D and the H-1 of Man-C. Additionally, we could find the NOE cross-peak D2Ј between the H-2 of Man-D and the H-1 of Man-E, of which the signal, 4.764 ppm, corresponds to the ␤-1,2-linked mannose unit (10,11,17). Using this procedure, we could sequentially assign the H-1 signal from Man-A to Man-E as A2-A2Ј-B2-B2Ј-C3-C3Ј-(or -C2-C2Ј-)-D2-D2Ј-E2.…”
Section: ␤-12-mannosyltransferase Of C Guilliermondiimentioning
confidence: 76%
See 4 more Smart Citations
“…Therefore, we can also assign through the H-1-H-2-correlated cross-peak C2 and the NOE cross-peak C2Ј between the H-2 of Man-D and the H-1 of Man-C. Additionally, we could find the NOE cross-peak D2Ј between the H-2 of Man-D and the H-1 of Man-E, of which the signal, 4.764 ppm, corresponds to the ␤-1,2-linked mannose unit (10,11,17). Using this procedure, we could sequentially assign the H-1 signal from Man-A to Man-E as A2-A2Ј-B2-B2Ј-C3-C3Ј-(or -C2-C2Ј-)-D2-D2Ј-E2.…”
Section: ␤-12-mannosyltransferase Of C Guilliermondiimentioning
confidence: 76%
“…The H-1 and H-2 signals of SaggMan 7 were sequentially assigned from Man-A to Man-F, A2-A2Ј-B2-B2Ј-C3-C3Ј-(or -C2-C2Ј-)-D2-D2Ј-E2-E2Ј-F2. It has been shown that the H-1 signal of an ␣-linked mannose unit substituted by two consecutive ␤-1,2-linked units causes an upfield shift (⌬␦ ϭ 0.02 ppm) (10,11,17,18). The H-1 proton of the Man-D of SaggMan 7 at 5.216 ppm appeared at about 0.02 ppm upfield from that of SagMan 6 at 5.239 ppm.…”
Section: ␤-12-mannosyltransferase Of C Guilliermondiimentioning
confidence: 99%
See 3 more Smart Citations